PENERAPAN MESIN SORTASI DALAM UPAYA EFESIENSI PROSES PRODUKSI KOPI GAYO SEBAGAI PRODUK UNGGULAN DAERAH ACEH TENGAH - Indra Mawardi; Hanif hanif; Jannifar Jennifar; Safaruddin Safaruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Gayo coffee is a superior regional product in the Central Aceh district. The production process of Gayo coffee is still done traditionally. In developing the quality and quantity of Gayo coffee, it is necessary to apply the production process technology. PKM activity partner, CV. Aceh nutrition has problems in the production process, especially in the sorting process, which is still manual. This process requires labor and long processing time so that the production process becomes inefficient. This problem is essential to be resolved in an effort to increase partner productivity. This service activity aims to improve the efficiency of the coffee bean production process through the application of a green bean sorting machine. The sorting machine will produce green beans based on size or dimensions following SNI. Solving partner problems is carried out using functional and structural approaches. Activities started from problem identification, design, and fabrication of green bean sorting machines, implementation and training, assistance, and evaluation. The results of these activities, green bean coffee sorting machines have been successfully fabricated with a capacity of 200-300 kg/hour. This machine has been implemented to partners CV. Nutrisi Aceh. The green bean sorting machine implemented to partners can operate well. The resulting large green beans amount to 30-40% of the total sorted green beans. The use of a sorting machine can increase the efficiency of time and labor in the green bean sorting process so that partner productivity can increaseABSTRAK:Kopi Gayo merupakan produk unggulan daerah kabupaten Aceh Tengah. Proses produksi kopi Gayo masih banyak dilakukan secara tradisional. Dalam pengembangan kualitas dan kuantitas kopi Gayo diperlukan penerapan teknologi proses produksi. Mitra kegiatan PKM, CV. Nutrisi Aceh memiliki permasalahan dalam proses produksi, khususnya pada proses penyortiran yang masih manual. Proses ini membutuhkan tenaga kerja dan waktu proses yang lama, sehingga proses produksi menjadi tidak efesien. Permasalahan ini menjadi penting untuk diselesaikan dalam upaya peningkatan produktivitas mitra. Tujuan kegiatan pengabdian ini adalah meningkatkan efesiensi proses produksi biji kopi melalui penerapan mesin sortasi green bean. Mesin sortasi akan menghasilkan green bean berdasarkan besar atau dimensi sesuai dengan SNI. Penyelesaian permasalahan mitra dilakukan dengan metode pendekatan fungsional dan struktural. Kegiatan dimulai dari identifikasi permasalahan, perancangan dan fabrikasi mesin sortasi green bean, implementasi dan pelatihan, pedampingan, dan evaluasi. Dari hasil kegiatan telah berhasil difabrikasi dan diimplemetasikan teknologi mesin sortir green bean kepada mitra. Penggunaan mesin sortir dapat meningkatkan efesiensi waktu dan tenaga kerja dalam proses penyortiran green bean sehingga produktivitas mitra dapat meningkat.